Promoting Inclusive Literacy through Teaching Practices for Students with Dyslexia in Primary School Settings - MALAHLELA, Moyagabo Kate; Masupe, Doreen Boikhutso (Universitas Negeri Semarang, 2025)
This study aligns with Sustainable Development Goal 4 and the United Nations Convention on the Rights of Persons with Disabilities, both of which advocate for inclusive and equitable quality education. It investigates teaching strategies that support inclusive literacy for students with dyslexia in primary school settings. Using a quantitative descriptive and correlational design, the research was conducted in five mainstream primary schools under Botswana's Ministry of Education and Skills Development. The sample comprised 143 teachers and school administrators involved in special education, selected through the Cochran formula. Data were collected via a standardized, self-administered questionnaire and analysed using SPSS. Findings revealed a strong positive correlation (R = 0.864) between inclusive literacy outcomes and factors such as teaching strategies, teacher preparation, inclusive practices, and resource availability. The regression analysis (F = 34.251) confirmed that these variables significantly predict literacy success for students with dyslexia. The study concludes that empowering teachers through systemic professional development is essential for fostering effective, inclusive education. It highlights the critical role of teacher preparedness in implementing inclusive literacy strategies and calls for targeted training programs to address the needs of students with dyslexia.